Legal feasibility of using constructed wetlands for wastewater treatment in social housing units in Xalapa, Veracruz, Mexico - Losada-Rodríguez, Nelson Andrés; Marín-Muñiz, José Luis; Celis-Pérez, María del Carmen; Zamora-Castro, Sergio; Ortega-Pineda, Gonzalo; Zitácuaro-Contreras, Irma (Renewable Energy, Biomass & Sustainability, 2024)
Constructed Wetlands (CWs) are a type of nature-based solution that uses ecological engineering to treat wastewater. The legal feasibility of implementing CWs as a treatment system in urban residential areas has been researched in various Latin American countries, including Chile, Peru, Colombia, Panama, and Guatemala. However, research regarding the legal feasibility of implementing CWs in urban areas, particularly in Multifamily Housing Units of Social Interest (MHUSI) in Mexico, was not found. Thus, this research aims to analyze the legal feasibility of CWs as wastewater treatment systems in the MHUSI of Xalapa, Veracruz, Mexico. To achieve this objective, a qualitative exploratory study was conducted. The study involved a documentary investigation to gather information about the background of the research, as well as content analysis to scrutinize legal documents such as laws, regulations, decrees, and Mexican Official Standards. The documental research focused on the search for regulatory documents, such as laws, regulations, decrees and standards, both at the federal level and at the state and municipal level. The content analysis focused on identifying the subsections, fractions and articles of the regulations found on water and sanitation, environmental impact and urban development applicable to the wastewater treatment systems of the MHUSI of Xalapa, Veracruz, Mexico. The research revealed that in Mexico, regulations mandate MHUSI to have a treatment plant in situations where it is not feasible to connect to the municipal sewage network. However, the use of CWs on a large scale to mitigate pollution from discharges has not been identified as a solution. After careful analysis, it has been determined that installing CWs wastewater treatment systems in MHUSI is legally feasible. In Veracruz, in terms of environmental impact, wastewater treatment systems no require an Environmental Impact Statement, which simplifies the procedures for this type of systems. In terms of urban development, MHUSI must incorporate a wastewater treatment system into their infrastructure. Regarding water and sanitation, no restrictions were found beyond guaranteeing compliance with the maximum permissible limits of contaminants established in Mexican standards. Finally, it was found that CWs are a method accepted by CONAGUA for the treatment of wastewater; in addition, this entity has a published manual and an inventory that includes them as a recognized process. However, it is crucial to ensure that the operation of these systems adheres to the regulations governing environmental impact and the permissible levels of contaminants in wastewater discharges to municipal sewage networks. This study is the first in Mexico to examine the legal viability of CWs as wastewater treatment systems in urban environments, specifically in MHUSI, providing a background that can contribute to the development of policies and regulations in this field. It is recommended to carry out technical, structural and financial feasibility studies to implement CWs in MHUSI in Xalapa, Veracruz, Mexico., aspects that were not addressed in this research.